The impact of chronic carbohydrate manipulation on mucosal immunity in elite endurance athletes - McKay, A. K. A.; Pyne, D. B.; Peeling, P.; Sharma, A. P.; Ross, M. L. R.; Burke, L. M. (Journal of Sports Sciences, 2019)
Carbohydrate (CHO) availability could alter mucosal immune responses to exercise. This study compared the effect of three dietary approaches to CHO availability on resting and post-exercise s-IgA levels. Elite race walkers (n = 26) adhered to a high CHO diet (HCHO), periodised CHO availability (PCHO) or a low CHO/high fat diet (LCHF) for 3 weeks while completing an intensified training program. HCHO and PCHO groups consumed 8.0-8.5 g/kg CHO daily, with timing of ingestion manipulated to alter CHO availability around key training sessions. The LCHF diet comprised 80% fat and restricted CHO to < 50 g/day. A race walk test protocol (19 km females, 25 km males) was completed at baseline, after adaptation, and following CHO restoration. On each occasion, saliva samples were obtained pre- and post-exercise to quantify s-IgA levels. Resting s-IgA secretion rate substantially increased ~ two-fold post-intervention in all groups (HCHO: 2.2 ± 2.2, PCHO: 2.8 ± 3.2, LCHF: 1.6 ± 1.6; fold-change± 95% confidence limits), however, no substantial differences between dietary treatments were evident. Post-exercise, substantial 20-130% increases in s-IgA concentration and 43-64% reductions in flow rate occurred in all dietary treatments, with trivial differences evident between groups. It appears that high volume training overrides any effect of manipulating CHO availability on mucosal immunity in elite athletes.